Incidence, risk factors, and outcomes of pulmonary hypertension in preterm infants with bronchopulmonary dysplasia. Issue 4 (10th March 2019) - MacKenzie, Katelyn; Cunningham, Kathy; Thomas, Sumesh; Mondal, Tapas; el Helou, Salhab; Shah, Prakesh S; Mukerji, Amit
Abstract: Objectives: To determine the incidence and risk factors for pulmonary hypertension (PH) in preterm infants with moderate to severe bronchopulmonary dysplasia (BPD) and to compare short-term outcomes. Methods: Preterm infants <32 weeks gestation born August 2013 through July 2015 with moderate to severe BPD at 36 weeks postmenstrual age were categorized into BPD-PH (exposure) and BPD-noPH (control) groups. Results: Of 92 infants with BPD, 87 had echocardiographic assessment, of whom 24 (28%) had PH. On multiple logistic regression after adjustment for gestational age and sex, no significant risk factors for PH were identified based on data from this cohort. There were no differences in resource utilization or clinical outcomes including survival to discharge. Conclusion: Approximately one out of four patients with moderate to severe BPD were identified as having PH. No significant risk factors for PH were identified. No differences in outcomes were identified for those with and without PH.